MANAGEMENT CROP PRODUCTION SYSTEM USING PRECISION FARMING CONCEPT FOR DECISION MAKING. - MANTOVANI, EVANDRO CHARTUNI; MATOSO, MARCOS JOAQUIM; OLIVEIRA, ANTONIO CARLOS DE; AVELLAR, GISELA DE (Revista Brasileira de Engenharia de Biossistemas, 2007)
The change of data into information is the most important aspects when using precision agriculture concept, in order to understand crop yield differences in the same area of production. The objective of this paper is to present a Management Crop Production System Methodology to help farmers make decisions of a specific intervention on the low production and unprofitable areas. This work was developed in Sete Lagoas, Minas Gerais state, Brazil, during three years (1999 through 2002), in an area of 38 ha, irrigated by a center pivot, with corn crop under no-tillage system and the results applied for developing a methodology and then applied to a production area of 115 ha, Recanto Farm, Sidrolândia, MS, Brazil. The yield maps were obtained using a MF-34 combine, with an yield monitor and DGPS system. The proposed methodology is being used to identify and to analyze the intervention areas by two maps: trend and profitability. This methodology provides the farmers with a management system to analyze a specific production variable or adopted technology, by accepting or rejecting a certain intervention.